How self leadership enhances normative commitment and work performance by engaging people at work? - Inam, Aneeq; Jo, Ann Ho; Sheikh, Adnan Ahmed; Shafqat, Marium; Najam, Usama (Springer Nature, 2021)
Leadership and its connection with social sustainability are frequently prescribed for effective management. Integrating selfleadership among the employees is an emerging area to focus on empowering an organization. The principal objective of this study was to empirically investigate the impact of self-leadership on normative commitment and work performance through the mediating role of work engagement. This phenomenon of self-leadership was explained by using the theoretical lens of the social cognitive theory and intrinsic motivation theory. Data was collected from 318 employees who worked in the telecom sector in Pakistan and analyzed using Structural Equation Modeling (SEM) AMOS. The findings revealed that in the presence of self-leadership, employee’s work engagement, commitment to the organization, and overall work performance elevated significantly. Furthermore, the results also illustrated the occurrence of two significant mediating paths. First, the mediating role of work engagement in the relationship between self-leadership and normative commitment, and second, the mediation of work engagement in the relationship between self-leadership and work performance. The findings of the study significantly contribute practically, and theoretically to the existing literature.